Epidemiological changes in cutaneous lymphomas: an analysis of 8593 patients from the French Cutaneous Lymphoma Registry. (29th November 2020) - Dobos, G.; de Masson, A.; Ram‐Wolff, C.; Beylot‐Barry, M.; Pham‐Ledard, A.; Ortonne, N.; Ingen‐Housz‐Oro, S.; Battistella, M.; d'Incan, M.; Rouanet, J.; Franck, F.; Vignon‐Pennamen, M.D.; et al.
Summary: Background: Primary cutaneous lymphomas (PCLs) are a heterogeneous group of T‐cell (CTCL) and B‐cell (CBCL) malignancies. Little is known about their epidemiology at initial presentation in Europe and about potential changes over time. Objectives: The aim of this retrospective study was to analyse the frequency of PCLs in the French Cutaneous Lymphoma Registry (GFELC) and to describe the demography of patients. Methods: Patients with a centrally validated diagnosis of primary PCL, diagnosed between 2005 and 2019, were included. Results: The calculated incidence was unprecedently high at 1·06 per 100 000 person‐years. The number of included patients increased yearly. Most PCL subtypes were more frequent in male patients, diagnosed at a median age of 60 years. The relative frequency of rare CTCL remained stable, the proportion of classical mycosis fungoides (MF) decreased, and the frequency of its variants (e.g. folliculotropic MF) increased. Similar patterns were observed for CBCL; for example, the proportion of marginal‐zone CBCL increased over time. Conclusions: Changes in PCL frequencies may be explained by the emergence of new diagnostic criteria and better description of the entities in the most recent PCL classification. Moreover, we propose that an algorithm should be developed to confirm the diagnosis of PCL by central validation of the cases. Abstract : What is already known about this topic? Primary cutaneous lymphomas (PCLs) are a heterogeneous group of diseases. Little is known about changes over time in their epidemiology and about patients' characteristics and disease stages at the initial presentation. What does this study add? In this population‐based study we present changes over time in PCL epidemiology over a 15‐year period and show an unprecedentedly high incidence in Europe. The relative frequency of rare PCL remained stable over time, while other PCL subtypes were better stratified. This study suggests that the diagnosis of PCL should be evoked more frequently, and delivers up‐to‐date information on patients' characteristics at initial diagnosis in a European population. Linked Comment:  Vermeer. Br J Dermatol 2021; 184 :993–994 .